2021
DOI: 10.33558/jrak.v12i2.2721
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of Intellectual Capital and Working Capital on Profitability of State-Owned Sharia Commercial Banks

Abstract: State-owned sharia commercial banks are the highest assets of Islamic banking in Indonesia. As a financial institution operating in a country that operates a dual banking system, it is required to compete with conventional banking. Facing fairly fierce competition, Islamic banking is required to manage all its capital to generate profitability. Both non-physical capital, intellectual capital (intellectual capital), knowledge, and physical capital to operate the company, namely working capital. The purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
2
4
0
1
Order By: Relevance
“…This study is consistent with studies done by Mardiah & Nurulrahmatiah, (2020) and (Wijaya, 2012) However, this research has not in line with the results of the study conducted by (Rosida & Aisyah, 2021;Widiyanti & Bakar, 2014).…”
Section: The Effect Of Working Capital Turnover On Profitabilitysupporting
confidence: 84%
See 1 more Smart Citation
“…This study is consistent with studies done by Mardiah & Nurulrahmatiah, (2020) and (Wijaya, 2012) However, this research has not in line with the results of the study conducted by (Rosida & Aisyah, 2021;Widiyanti & Bakar, 2014).…”
Section: The Effect Of Working Capital Turnover On Profitabilitysupporting
confidence: 84%
“…So that it can compete more effectively with other businesses. This study is consistent with studies done by (Asare et al, 2017;Gupta et al, 2020;Rosida & Aisyah, 2021;Tiwari, 2022;Wijayani, 2017). However, this research has not in line with the results of the study conducted by (Malaya & Jiwa, 2018;M.…”
Section: The Effect Of Intellectual Capital On Profitabilitysupporting
confidence: 84%
“…Penelitian mengenai pengaruh intellectual capital terhadap profitabilitas baik dilihat dari profitabilitas secara umum, ROA, return on equity (ROE) dan earning per share (EPS) sudah diteliti oleh Wany (2010); Wijaya (2012); Asiah (2014); Dwipayani and Prastiwi (2014); Faza and Hidayah (2014); Budiasih (2015); Cahyani, S., and Ferdiana (2015); Bustamam and Aditia (2016); Fadri and Wahidahwati (2016); Halim, Basri, and Faisal (2016); Santoso, Djaelani, and Destryanti (2017); Astuti, Sarda, and Muchran (2019); Putri and Gunawan (2019); Wardani, Widarno, and Kristianto (2020); Farihah and Setiawan (2020); Rahayu, Kurniati, and Wahyuni (2020); Rosida and Aisyah (2021) dengan hasil yang berbeda-beda. Namun penelitian tersebut tidak mengkaji pengaruh faktor intellectual capital secara detail terhadap profitalilitas yang diproksikan dengan VACA, VAHU, dan STVA serta perspektif syariah.…”
Section: Pendahuluanunclassified
“…Research gaps have been found in the results of these studies to fill these gaps. This research can explain the analysis of Rosida & Aisyah (2021) to re-examine the influence of intellectual capital on financial performance and provide evidence of the components of intellectual capital and financial performance of Islamic banking in Indonesia. Which component gives the greatest contribution to the assessment of intellectual capital and financial performance?…”
Section: Introductionmentioning
confidence: 97%
“…Many research results prove that intellectual capital affects company performance (Rosida & Aisyah, 2021;Susanti et al, 2020;Xu & Wang, 2018;Nadeem et al, 2018;Simarmata & Subowo, 2016;Ousama & Fatima, 2015;Gozali & Hatane, 2014). In the context of banking in Indonesia, there are still differences in research results, both in the advantages of each component of intellectual capital and its relationship (positive/negative) to banking financial performance.…”
Section: Introductionmentioning
confidence: 99%